Incidence and economic burden of prosthetic joint infections in a university hospital: A report from a middle-income country - Emine Alp; Fatma Cevahir; Safiye Ersoy; Ahmet Guney (Elsevier, 2016)
Summary: In this study, we aimed to evaluate the incidence and economic burden of prosthetic joint infections (PJIs) in a university hospital in a middle-income country. Surveillance data between April 2011 and April 2013 in the Orthopedic Surgery Department was evaluated. Patients (>16 years old) who had primary arthroplasty in Erciyes University were included in the study, and patients with preoperative infection were excluded. Patients were followed up during their stay in the hospital and during readmission to the hospital for PJI by a trained Infection Control Nurse. During the study period, 670 patients were followed up. There were 420 patients (62.7%) with total hip arthroplasty (THA), 241 (36.0%) with total knee arthroplasty (TKA) and 9 (1.3%) with shoulder arthroplasty (SA). The median age was 64, and 70.6% were female. The incidence of PJI was 1.2% (5/420) in THA, 4.6% (11/241) in TKA and 0% (0/9) in SA. PJI was significantly more prevalent in TKA (p = 0.029). All of the PJIs showed early infection, and the median time for the development of PJI was 23.5 days (range 7-120 days). The median total length of the hospital stay was seven times higher in PJI patients than patients without PJI (49 vs. 7 days, p = 0.001, retrospectively). All hospital costs were 2- to 24-fold higher in patients with PJI than in those without PJI (p = 0.001). In conclusion, the incidence and economic burden of PJI was high. Implementing a national surveillance system and infection control protocols in hospitals is essential for the prevention of PJI and a cost-effective solution for the healthcare system in low-middle-income countries. Keywords: Arthroplasty, Infection control, Operating rooms, Incidence, Cost